The western european point of view about the other one: a paradigm of science - Santos, Jéssica Fernandes Maia dos (2013)
Looking the Levi-Strauss’s works The Savage Mind and Totemism Today, and Edward Said’s Orientalism, this paper aims to propose a reflection on the historical European thought regarding the alterity, how it was build and how it still is an science paradigm. According to Levi-Strauss, the institutionalization of the totemism would be a false analysis category in which the European, by classifying and typifying the foreign people while totemic organizations designed their own universe. This concept considers the other people as their opposite side, without having a conceptual consensus of that would be a totemic organization. The same does the evolutionism, which has influenced not only the totemic institution but also the whole western thinking.